Characteristics of chemical composition and source apportionment of PM2.5 during a regional haze episode in the yangtze river delta, china - Diao, Yiwei; Liu, Ankang; Hu, Qun; Yang, Meng; Zhao, Tianliang; Cui, Yi; Shi, Shuangshuang; Kong, Xiangchen (Frontiers in Environmental Science, 2022)
The source of PM2.5 varies at different stages of urban haze pollution. In addition, there is obvious regional transport of pollutants between urban agglomerations. PM2.5 and its major chemical compositions in a regional haze episode were measured continuously from 16 to 27 November 2018 in Nanjing, China. The types of main sources resolved by principal component analysis (PCA) and positive matrix factorization (PMF) were similar, and the result of PMF was more refined. The average contribution of each source by PMF was: secondary nitrate (64.01%), secondary sulfate (11.62%), incomplete combustion (4.49%), sea salt (8.61%), biomass burning (6.90%), and crustal dust (4.37%). The distribution characteristics of air pollutants differed in different haze stages. The concentrations of SO42-, NO3-, NH4+, and black carbon (BC) were the highest in haze development, which was 2.0, 3.1, 3.0, and 2.4 times higher than the clean stage, respectively. The increase of NO3- dominated the development of haze, and the proportion of NO3- from haze generation to development increased by 4.05%. Concentration contributions of secondary nitrate, sea salt, and biomass burning were highest in haze development, secondary sulfate was highest in haze generation, and incomplete combustion was highest in haze dissipation, which was 3.5, 1.8, 3.3, 1.7, and 9.5 times higher than the clean stage, respectively. The contribution of crustal dust in the whole haze episode was lower than in the clean stage. Potential source contribution function (PSCF) and concentration weighted trajectory (CWT) revealed that the major source area of air pollutants in Nanjing was from the southeast, and the major impact area was in the northwest.